The chemical components, action mechanisms, and clinical evidences of YiQiFuMai injection in the treatment of heart failure - Lv, Shichao; Wang, Yunjiao; Zhang, Wanqin; Shang, Hongcai (Frontiers in Pharmacology, 2022)
YiQiFuMai injection (YQFM), derived from Shengmai Powder, is wildly applied in the treatment of cardiovascular diseases, such as coronary heart disease and chronic cardiac insufficiency. YQFM is mainly composed of Radix of Panax ginseng C.A. Mey. (Araliaceae), Radix of Ophiopogon japonicus (Thunb.) Ker Gawl (Liliaceae), and Fructus of Schisandra chinensis (Turcz.) Baill (Schisandraceae), and Triterpene saponins, steroidal saponins, lignans, and flavonoids play the vital role in the potency and efficacy. Long-term clinical practice has confirmed the positive effect of YQFM in the treatment of heart failure, and few adverse events have been reported. In addition, the protective effect of YQFM is related to the regulation of mitochondrial function, anti-apoptosis, amelioration of oxidant stress, inhibiting the expression of inflammatory mediators, regulating the expression of miRNAs, maintaining the balance of matrix metalloproteinases / tissue inhibitor of metalloproteinases (MMP / TIMP) and anti-hypoxia.